2021
DOI: 10.1038/s41416-021-01519-2
|View full text |Cite
|
Sign up to set email alerts
|

Coregulation of pathways in lung cancer patients with EGFR mutation: therapeutic opportunities

Abstract: Epidermal growth factor receptor (EGFR) mutations in lung adenocarcinoma are a frequent class of driver mutations. Single EGFR tyrosine kinase inhibitor (TKI) provides substantial clinical benefit, but almost nil radiographic complete responses. Patients invariably progress, although survival can reach several years with post-treatment therapies, including EGFR TKIs, chemotherapy or other procedures. Endeavours have been clinically oriented to manage the acquisition of EGFR TKI-resistant mutations; however, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 91 publications
1
21
0
Order By: Relevance
“…However, thirdgeneration EGFR-TKIs still cannot prevent the development of acquired resistance due to persistent mutations in the gene (Lee, 2017;Remon et al, 2018). An increasing number of studies have shown that combining existing small molecule anticancer drugs with EGFR-TKIs can circumvent acquired drug resistance and enhance the antitumor effects of EGFR-TKIs through a bypass signaling mechanism (Rosell et al, 2021). In the present study, we found that the combination of EGFR-TKIs and SAHA is a potential treatment option to reverse the acquired resistance of EGFR-TKIs in NSCLC.…”
Section: Discussionmentioning
confidence: 50%
“…However, thirdgeneration EGFR-TKIs still cannot prevent the development of acquired resistance due to persistent mutations in the gene (Lee, 2017;Remon et al, 2018). An increasing number of studies have shown that combining existing small molecule anticancer drugs with EGFR-TKIs can circumvent acquired drug resistance and enhance the antitumor effects of EGFR-TKIs through a bypass signaling mechanism (Rosell et al, 2021). In the present study, we found that the combination of EGFR-TKIs and SAHA is a potential treatment option to reverse the acquired resistance of EGFR-TKIs in NSCLC.…”
Section: Discussionmentioning
confidence: 50%
“…The morbidity and mortality of LADC are increasing year-on-year due to early tumor recurrence, enhanced resistance to chemoradiotherapy, and rapid progression of the disease (62). Chemotherapy targeting mutated tyrosine kinase inhibitors (TKIs) of the epidermal growth factor receptor (EGFR) has recently become the main strategic treatment for LADC patients, such as in gefitinib, erlotinib, and afatinib (63). Joseph et al (43) discovered that SUMO-activating enzyme subunit 1 (SAE1) and circCCDC66 were highly expressed in LADC.…”
Section: Circccdc66 and Lung Cancermentioning
confidence: 99%
“…As genetic sequencing techniques are increasingly available, oncogenic driver mutations and other genomic alterations are frequently identified, guiding cancer therapy (4). In case of women of reproductive age, there are higher probabilities for harbored epidermal growth factor receptor (EGFR) mutations (5,6).…”
Section: Introductionmentioning
confidence: 99%